The Holy See’s Contemporary Foreign Policy: Origins, Methods, Instruments - E. O. Shebalina (Международная аналитика)
In this essay, the author made an attempt to study the origins, functions and vectors of papal diplomacy, focusing on its transformation in the conditions of the modern political system, to analyze the main social principles on which the foreign policy of the Holy See is based; to fi nd out what methods are used by the state to promote Christian moral values in global politics. Besides, studying numerous examples of mediation policy of the Vatican in international aff airs, the author has investigated the methods by which the theocratic monarchy, lacking signifi cant territorial and military resources, plays a signifi cant role in contemporary international relations. Papal diplomacy, as one of the fi rst in the world, has successfully adapted to the processes taking place in world politics. Based on the basic principles stemming from the Code of Canon Law and the Social Doctrine of the Roman Catholic Church, the Holy See participates in most of the international negotiation platforms where topical issues of world politics are raised.